2017
DOI: 10.2147/ott.s139252
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in clinicopathological features and survival of patients with primary urethral carcinoma: a population-based study

Abstract: PurposeTo analyze the Surveillance, Epidemiology, and End Results (SEER) database to determine the effects of sex and prognostic factors on the survival of patients with primary urethral carcinoma (PUC).Materials and methodsWe selected 453 patients diagnosed with PUC from 2004 to 2013 from the SEER database. Statistical analysis was used to identify sex-specific differences associated with tumor characteristics and cancer-specific survival (CSS) and overall survival (OS).ResultsCompared with men, there was a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
(39 reference statements)
4
10
0
Order By: Relevance
“…In this study, there was no difference in prognosis between men and women, which has also been confirmed in other studies 13,14. However, although SCC is most common among women,15 studies have reported that women’s prognosis is poorer than that of men in AC 13.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, there was no difference in prognosis between men and women, which has also been confirmed in other studies 13,14. However, although SCC is most common among women,15 studies have reported that women’s prognosis is poorer than that of men in AC 13.…”
Section: Discussionsupporting
confidence: 90%
“…However, although SCC is most common among women,15 studies have reported that women’s prognosis is poorer than that of men in AC 13. There have also been reports of higher clinical stages of AC in Black women than men 14. In the USA, the onset time of male and female urethral cancer is approximately 60 years 15,16.…”
Section: Discussionmentioning
confidence: 99%
“…A positive effect of the combination of surgery and RT compared with monotherapy has been reported previously [41]. While surgery alone was associated with better CSS than RT alone in the SEER studies of Rabbani [17] (p = 0.018) and Champ et al [12] (p = 0.001), Wei et al [19] found surgery to be an independent factor for better OS and CSS in women treated with RT (p = 0.003). Furthermore, Son et al [18] reported that in the NCDB cohort, the absence of local therapy (surgery and/or RT) was an independent factor for worse OS (no p value reported).…”
Section: Influence Of Rt On Survival Outcomesmentioning
confidence: 64%
“…A total of 12 studies with 7853 patients were included according to the statement of Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) protocols ( Fig. 1, and Tables 1 and 2) [11][12][13][14][15][16][17][18][19][20]. Two large multicentric studies reported on the same cohort [14,15].…”
Section: Evidence Synthesismentioning
confidence: 99%
“…These tumours have an aggressive natural history, with reported 5‐year overall survival rates of 32–54% [2,3,7,8]. Patient and tumour characteristics associated with oncological outcome include sex, age, tumour location, stage and nodal status [2,3,5,9,10].…”
Section: Introductionmentioning
confidence: 99%